Effect of stacking sequences on mechanical properties of kenaf hybrid composites - Yusuff, Mohamad Ikhwan; Sarifuddin, Norshahida; Mohd Ali, Afifah; Ismail, Hanafi; Mohamad, Siti Norbahiyyah (Trans Tech Publications Ltd, 2020)
In the current project, Kenaf fiber (K) and carbon fiber (C) with epoxy resin were utilized to form carbon-kenaf hybrid composites using a vacuum infusion technique. The volume fraction of fiber and thickness of a hybrid composite was fixed at 40 vol.% and 3mm, respectively. Four different sequences were introduced in the current project including CCCCC, KKKKK, KCKCK, and CKCKC. Mechanical testing such as tensile and flexural tests were performed according to ASTM D3039 and ASTM D790, respectively. Scanning Electron Microscope (SEM) and Optical Microscope (OM) were used to identify modes of failures in both tensile and flexural tests of carbon/kenaf hybrid composites. The hybrid CKCKC sample displayed a higher value in tensile strength (264.23 MPa), tensile modulus (11.06 GPa), flexural strength (438.51 MPa) and flexural modulus (25.13 GPa) as compared than KCKCK hybrid sample.